A Role for the Cavin-3/Matrix Metalloproteinase-9 Signaling Axis in the Regulation of PMA-Activated Human HT1080 Fibrosarcoma Cell Neoplastic Phenotype - Toufaily, Chirine (Cancer Growth Metastasis, 2014)
Caveolae are specialized cell membrane invaginations known to regulate several cancer cell functions and oncogenic signaling pathways. Among other caveolar proteins, they are characterized by the presence of proteins of the cavin family. In this study, we assessed the impact of cavin-1, cavin-2, and cavin-3 on cell migration in a human HT-1080 fibrosarcoma model. We found that all cavin-1, -2 and -3 transcripts were expressed and that treatment with phorbol 12-myristate 13-acetate (PMA), which is known to prime cell migration and proliferation, specifically upregulated cavin-3 gene and protein expression. PMA also triggered matrix metalloproteinase (MMP)-9 secretion, but reduced the global cell migration index. Overexpression of recombinant forms of the three cavins demonstrated that only cavin-3 was able to reduce basal cell migration, and this anti-migratory effect was potentiated by PMA. Interestingly, cavin-3 overexpression inhibited PMA-induced MMP-9, while cavin-3 gene silencing led to an increase in MMP-9 gene expression and secretion. Furthermore, recombinant cavin-3 significantly prevented PMA-mediated dephosphorylation of AKT, a crucial regulator in MMP-9 transcription. In conclusion, our results demonstrate that cellular cavin-3 expression may repress MMP-9 transcriptional regulation in part through AKT. We suggest that the balance in cavin-3-to-MMP-9 expression regulates the extent of extracellular matrix degradation, confirming the tumor-suppressive role of cavin-3 in controlling the invasive potential of human fibrosarcoma cells.